2021
DOI: 10.1002/hed.26791
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis on the association of mental health disorders with in‐hospital postoperative complications and mortality in head and neck cancer surgery

Abstract: Background The objective was to assess the association of mental health disorders with in‐hospital complication and mortality rates in patients undergoing head and neck cancer surgery. Methods In this exploratory retrospective study, the Nationwide Inpatient Sample was queried from 2003 to 2014 for all patients with a diagnosis of head and neck cancer who underwent surgery. Univariate cross‐tabulation, logistic regression, and propensity score matching (PSM) were used to compare demographics, procedure‐related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…29 For head and neck cancer surgery, patients with MHD had higher risk of overall complications (OR 1.28, 95% CI 1.12-1.46, P < .001). 27 For non-emergent patients with psychiatric illness undergoing laparoscopic cholecystectomies, complications were increased post-operatively (OR 8.6; 95% CI 1.7-39.1, P = .01). 28…”
Section: Resultsmentioning
confidence: 95%
“…29 For head and neck cancer surgery, patients with MHD had higher risk of overall complications (OR 1.28, 95% CI 1.12-1.46, P < .001). 27 For non-emergent patients with psychiatric illness undergoing laparoscopic cholecystectomies, complications were increased post-operatively (OR 8.6; 95% CI 1.7-39.1, P = .01). 28…”
Section: Resultsmentioning
confidence: 95%
“…recognised the preoperative period as a timepoint within the surgical journey where supportive treatment could potentially improve a person's surgical outcomes 67 . Studies have demonstrated the benefits of meditation and mindfulness coaching alongside mental health consultations during the treatment pathways for surgical cancer populations, including breast, prostate, head and neck, and lung cancer 68–71 . Continued psychological support, including the integration of mindfulness‐based interventions post‐operatively, may also be of benefit for this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional analysis of United States hospital discharge data from the National (Nationwide) Inpatient Sample (NIS) database including 85,440 patients from 2008 to 2013 showed an in-hospital mortality rate of 4.2% [ 7 ]. The NIS was also used to analyze the association of mental health disorders with in-hospital and mortality in head and neck cancer surgery [ 8 ]. In the NIS data, mental health disorders were not associated to higher risk of early mortality in patients who underwent surgery from 2003 to 2014 for HNC.…”
Section: Introductionmentioning
confidence: 99%